A highly efficient and transparent luminescent solar concentrator based on a nanosized metal cluster luminophore anchored on polymers. Issue 11 (2nd March 2022) - Choi, Jun; Nguyen, Dieu; Gi, Eunbyeol; Brylev, Konstantin A.; Yu, Ji Woong; Kim, Dawoon; Lee, Won Bo; Kim, Dong Ha; Chung, In; Kim, Kyung Kon; Kim, Sung-Jin
Abstract : Organic–inorganic nano-sized hexanuclear complexes were copolymerized with PMMA to generate a LSC device with a high efficiency up to 1.24% and a transparency >85%. Our LSC suggests a practical future direction for smart windows. Abstract : A highly efficient luminescent solar concentrator (LSC) composed of a nanosized metal-cluster as a molecular luminophore copolymerized with poly(methyl methacrylate) (PMMA) was fabricated through a simple solution process. Organic–inorganic salts such as (dMDAEMA)2 [Mo6 Cl14 ] and (dMDAEMA)2 [Mo6 I14 ] (where dMDAEMA is 2-(methacryloyloxy)ethyl dimethyldodecylammonium) were copolymerized with PMMA to generate a highly effective, transparent, and robust LSC waveguide. This hybrid luminophore enabled the development of a highly efficient UV-vis sunlight harvesting device due to strong absorption at UV-vis wavelengths up to ∼500 nm and a large downshift of luminescence at near-infrared wavelengths (∼850 nm). Si photovoltaic cells were placed at the edge of the LSC waveguide plate to collect the concentrated luminescence by internal reflection. LSCs fabricated with a 2.0 × 2.0 × 0.3 mm 3 size had the highest observed power conversion efficiency (PCE) of 1.24% and a transparency of ∼85%, which were much higher than those of LSCs made from other luminophores with the same Si photovoltaic cell. Our LSC with chemical/physical durability, robustness, and solution processability for any desirable plate size and thickness suggests a practical future direction for smart windows of urban buildings where traditional Si photovoltaic cells cannot be directly employed.